Sistem Informasi Penggajian Pegawai Secara Multiuser Pada STIKES Duta Gama Klaten - Bayu Hartono, Muh. Hasbi, Tri Irawati (STMIK Sinar Nusantara, 2014)
Sekolah Tinggi Ilmu Kesehatan (STIKES) Duta Gama Klaten which has developed rapidly in 5 (five) years. Along with these developments, followed by an increase in Human Resources. At the end of each month STIKES Duta Gama Klaten do payroll for all employees. Payroll system includes several interrelated parts that public administration is responsible regarding the presence recap, responsible for financial administration of payroll management and Chairman Duta Gama STIKES Klaten in charge. The payroll system is still done manually so that the salary calculation process takes a long time.Payroll information system development process carried out by several phases : problem formulation, planning, problem solving, creation of information systems payroll and payroll information system testing. Of research by the author produced a program employee payroll information system applications in multiuser containing employee data report, the data position, the data class, presence of data, the data overtime, the data overtime and payroll reports. Keywords: Design, employee payroll, Visual FoxPro.